Fiscal Policy, Monetary Regimes and Current Account Dynamics - Stefan Hohberger; Bernhard Herz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The paper examines the stabilizing properties of fiscal policy for current account imbalances under alternative exchange rate regimes. Using a small open economy DSGE model with fiscal feedback rules, we investigate the dynamic responses of different shocks to macroeconomic variables and their implication for the current account. Our results imply that a fiscal response to the current account improves the stabilizing effect of most macroeconomic variables compared to a countercyclical response to output. The loss of national monetary policy when entering into a monetary union leads to higher variability and more persistence of the real exchange rate and the current account. Despite the stabilizing properties, fiscal policy intervention induces higher variability of output in the short-run and therefore faces a trade-off between stabilizing the external position and output
Keywords: E62; F41; E61; 330